Solving RE models with discontinuous policy rules – an application to minimum wage setting in Germany - Dirk Bursian (Deutsche Bundesbank, 2016)
The legal regulations require the minimum wage in Germany to be adjusted biennially which gives rise to a policy discontinuity. From the perspective of rational expectations models, such policy features render standard local approximation techniques infeasible. The paper presents a stylised model in which negotiated wages and corporate profits are the outcome of an optimisation problem, while changes to the minimum wage are modelled by a discontinuous policy rule. Using the simple example of minimum wage setting in Germany, the paper illustrates how such models can be solved using the method of undetermined coefficients and presents selected simulation results.
Keywords: E1; E6; 330; rational expectations model; discontinuous policy rule; method of undetermined coefficients